Aspirin is used to mitigate the increasing frequency of marathon-related cardiac arrests - Arthur J Siegel (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
Male gender and the marathon were shown to be independent and significant risk factors for cardiac arrest in United States road races in a 10-year registry beginning in 2000, during which events increased in frequency during the latter half of the study [1]. Fifty-nine fatalities in runners with an average age in the mid-40s indicate excess pre-mature acute mortality despite an overall incidence of 1 per 100,000 participants.